High-Speed and Wide-Field Photometry with TORTORA - G. Greco; G. Beskin; S. Karpov; S. Bondar; C. Bartolini; A. Guarnieri; A. Piccioni (Advances in Astronomy)
We present the photometric analysis of the extended sky fields observed by the TORTORA optical monitoring system. The technology involved in the TORTORA camera is based on the use of a fast TV-CCD matrix with an image intensifier. This approach can both significantly reduce the readout noise and shorten the focal length following to monitor relatively large sky regions with high temporal resolution and adequate detection limit. The performance of the system has been tested using the relative magnitudes of standard stars by means of long image sequences collected at different airmasses and at various intensities of the moon illumination. As expected from the previous laboratory measurements, artifact sources are negligible and do not affect the photometric results. The following analysis is based on a large sample of images acquired by the TORTORA instrument since July 2006.